Pembinaan Dan Kesan Modul Kaunseling Brief (Mkb-b) Terhadap Kebimbangan Dan Kadar Ponteng Dalam Kalangan Mangsa Buli - Mohd Saad, Mohamad Basri (2021)
This study aims to develop and identify the effect of Brief Counseling Module (MKB-b) on anxiety and truancy rate among bully-victims. Anxiety aspect is found to have a negative effect on bully-victims especially on their emotion and there is a potential for them to develop behavioural characteristics such as passive, sensitive, quiet, fragile, depressed etc. Other than that, truancy is reported to have a relation to bullying incident experienced by bully-victims. This study focuses on six objectives: determine the validity and reliability of counseling modules built in the study, develop the profiles of bully victims who suffer from anxiety and play truant, study the effects of the modules built on the score of anxiety and truancy rate and identify the factors that lead to changes in the anxiety scores and truancy rate among the participants. This study uses a mixed-method approach with the bigger approach given to the qualitative approach (QUAL-Quan). The sampling technique was used to select six primary secondary students in the three secondary schools involved in the study. This study uses the Hamilton Anxiety Rating Scale Inventory (HAM-A) instrument to measure the levels of anxiety among the study participants and also to record students' attendance to identify the truancy rates at respective schools involved. In addition to the HAM-A instruments and students’ attendance records, the researcher also obtained data from this study from counseling session transcription, module validity form, module reliability form, clients’ information form and counselors’ observation notes.